Avaliação fenotípica de células musculares lisas vasculares de aorta de ratos estimuladas por lipopolissacarídeo - Strela, Felipe Bichi (2018)
Introduction: Sepsis is defined as a potentially fatal organic dysfunction caused by a dysregulated host response to infection. It presents an increasing incidence and number of survivors in the last two decades, and these survivors are at high risk of developing complications, such as cardiovascular events, and increased mortality in the years following sepsis. Lipopolysaccharide (LPS) activates Toll-like receptor 4 (TLR4), contributing to the inflammatory response in sepsis. TLR4 is also expressed in vascular smooth muscle cells (VSMCs), and can modulate the phenotypic profile of these, and, cooperate for the pathophysiology of sepsis and cardiovascular changes in post sepsis. Objective: To evaluate the effects of LPS stimulation on different CMLV phenotypes, in culture. Methods: Primary aortic VSMCs from Wistar rats were incubated with LPS (1μg/mL) in different experimental protocols. Two incubation conditions were used in cell contraction and migration assays: (1) acute stimulation: stimulus initiated in the assays; (2) Preconditioning: stimulation for 24 or 48 hours and withdrawal of the stimulus in the assays. Cell migration and contraction were evaluated using the wound-healing and collagen gel contraction methods, respectively. Nitric oxide production by the Griess reaction, cytokine, vimentin, collagen and SM-22α genic expression by RT-PCR, and IL-6 production by ELISA were also evaluated. Results: Incubation with LPS for 6 hours increased the expression of cytokines (IL-1β: 794%, IL-6: 2310%, TNFα: 380%, MCP-1: 99%), and for 24 hours increased the gene expression of secretory phenotype markers (collagen: 27%, vimentin: 29%) and SM22α (53%), a molecule related to migration and cell contraction. LPS increased IL-6 secretion after 24 hours (487%) and 48 hours (418%), and NO secretion after 8 hours (8%) and 24 hours (52%), these increases in NO production reversed by aminoguanidine (iNOS inhibitor). Acute stimulation with LPS reduced migration (-20%) and contraction (-38%), reversed by aminoguanidine. Pre-conditioning with LPS increased the migration (16%) and the contraction (154%) of the VSMCs, which were reversed with tocilizumab (IL-6 receptor inhibitor). Conclusion: LPS exerts effects modulating the secretory, contractile and migratory phenotypes. Acute stimulation with LPS promoted nitric oxide-dependent reduction of migratory and contractile response, suggesting that the acute responses of VSMCs to LPS may contribute to the pathophysiology of sepsis. 12 On the other hand, pre-conditioning with LPS promoted IL-6-dependent increases in the migration and contraction of VSMCs, with a possible participation of SM22α, evidencing that these cells even after discontinuation of the stimulus present phenotype modifications that may contribute to the occurrence of cardiovascular events